ANALISIS DAN DESAIN WING UAV VTOL MENGGUNAKAN FINITE ELEMENT ANALYSIS - Andika wijaya; Edi Sofyan; Ferry setiawan; Muhammad Kevin Adam (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2023)
Unmanned Aircraft (PTTA) or Unmanned Aerial Vehicle (UAV) is an aircraft that flies without a pilot and is controlled automatically. UAVs have a wide range of applications, including remote sensing, communication links, and natural disaster monitoring. One type of UAV being developed is LSU 05, using a composite of carbon fiber (CFRP) and glass fiber (GFRP) for its wing structure. This study aims to create a 3D model of the UAV VTOL wing, analyze the effect of material variations on the strength of the wing structure, and find the optimal wing design using the finite element analysis method. This study uses the SolidWorks 2021 software with maneuver conditions loading. The results of the analysis show that carbon fiber provides higher strength than fiberglass. In a fiberglass wing, the maximum stress is 229 MPa, while in a carbon fiber wing it is 197 MPa. The biggest displacement occurred in the fiberglass wing, which was 2.661 mm. The safety factor of the carbon fiber wing is 2.7, while that of the fiberglass is 1.9. This research provides an in-depth understanding of the behavior of VTOL UAV wing structures and contributes to the development of better wing designs. The optimized design can increase the performance, efficiency and reliability of VTOL UAV.